TEACHING STRUCTURE-BASED DRILLS AND COMMUNICATIVE DRILLS AT THE PRIMARY EDUCATION IN THE EFL SETTINGS - Arniatika, Sefvirda (Sanata Dharma University Yogyakarta, 2023)
This paper investigated the differences between two teaching techniques: structure-based and communicative drills in students’ speaking achievement and the improvement of speaking aspects after implementing those two techniques. The researcher employed the experimental design in this present study. A purposive sampling was used to choose the samples of one primary education in East Lampung, Indonesia. To gather the data, the researcher used the instrument of the test. The data were analyzed by using the Indpendent-Samples T Test and Paired-Samples T-Test. The results of the study showed that there was any statistically significant difference in students’ speaking achievement between the experimental class and the control class (.004.05) and those two different techniques had improved some aspects of speaking skills in terms of grammar, vocabulary, comprehension, pronunciation and tasks.